Policymaking in the Times of Social Media: What Has Changed in India? A Study of Telecom Sector ‘s e-Consultation Efforts - Thakur Varma, Sangita; Devi Mishra, Kaveri (International Journal of Psychosocial Rehabilitation, 2019)
Purpose: This paper aims to study the changes in policymaking brought about by the Government of India‘s adoption and promotion of social media under its Framework & Guidelines for Use of Social Media for Government Organisations (2012). The government states therein that ―the objective for the use of social media is not just to disseminate information but also to undertake public engagement for a meaningful public participation for formulation of public policy‖. The paper aims to capture the changes brought about in the policymaking and governance space as a result of the government opening up online communications channels (social media) with the citizenry. Through a case study of the Telecom Regulatory Authority of India‘s e-consultation process, this paper attempts to find out ―the integration of social media environment in policy consultations‖ in India. Methodology/Approach: The paper through a review of literature first explores the concept of social media and establishes whether the current government websites fall in the domain of social media. It reviews how social media is being utilized by various governments across the world in the governance and public policy domain. It then through the case study of Telecom Authority of India website explores e-consultancy in the policy-making domain and analyses the changes brought about with social media. A random analysis of six TRAI consultancy papers is conducted. The methodology adopted includes content analysis of relevant online platforms of TRAI and stakeholder survey to explores citizens‘ perceptions of pre-legislative consultation. The paper then identifies the limitations/lacunae of the current social media use by TRAI. Findings: The paper finds that TRAI website has social media functionalities embedded and is functioning as social media platform to promote participative policy making. However, it finds there are limitations in the approach brought about by lack of active promotion of pre-legislative consultation on external social media platforms. While the TRAI website is a vibrant interactive space, external social media platforms are being used to broadcast official information and for self-promotion. There is little or no attempt to actively engage stakeholders. Although TRAI is at the forefront of pre-legislative consultation online, there is not much action on its other social media functionalities like discussion forum. Research limitations: The paper studies just one government website for government‘s participative policymaking activity using social media. More websites will be studied as part of ongoing research by the author to develop a more holistic picture Practical implications: The paper posits that government websites are social media if they have functionalities of social media embedded and the activities on the website promote networked and participative governance. This opens up space for further research in the field on how government websites can be made social media and used to promote participatory democracy. Secondly, the paper explores how the government has appropriated the media space via its web 2.0 websites and its presence on social media. This line of thinking can be explored further. There is very little literature on Indian governments experiments with social media. The field is vast, and its exploration can yield explosive results with vast implications. Fourth, the study of pre-legislative consultation on web 2.0 websites of the Government of India has deep implications for participatory democracy. Originality/Value: This exploratory paper sets the path for further research in the field in India and contributes to the development of knowledge on the use of social media by governments to promote democratic values, trust and transparency.